Pengaruh Kombinasi Fungi Mikoriza Arbuskular dengan Kompos Kotoran Sapi terhadap Pertumbuhan dan Kadar N, P, K Kelapa Sawit Menghasilkan - Toto Suryanto; Hafisha Qori Panjaitan (JURNAL CITRA WIDYA EDUKASI, 2021)
Plant growth can be increased with balanced fertilization. Various types of fertilizers can be used to increase the availability of nutrients in the soil such as manure and biological fertilizers. This research aims to determine the effects and best dose of combined with cow dung compost on the growth and nutrient content of mature oil palm. This research was conducted at Teaching Farm of Politeknik Kelapa Sawit Citra Widya Edukasi, Bekasi from December 2019 to July 2020. The research used descriptive method with 3 treatments: 50 kg cow dung, 50 kg cow dung + 500 gr fungi michoriza, and 50 kg cow dung + 1000 gr fungi michoriza. The result showed that the results of measurements of all growth parameters and nutrient levels of N, P, and K showed an increase before and after being given fungi michoriza arbuscula and cow dung compost and the best dose of fungi michoriza arbuscula for the growth of palm oil yields was 1000 g mycorrhizal.